Evaluating pictorial support in person-centred care for children (PicPecc): a protocol for a crossover design study. Issue 5 (4th May 2021) - Nilsson, Stefan; Wiljén, Angelica; Bergquist, Jonas; Chaplin, John; Johnson, Ensa; Karlsson, Katarina; Lindroth, Tomas; Schwarz, Anneli; Stenmarker, Margaretha; Thunberg, Gunilla; Esplana, Linda; Frid, Eva; et al.
Abstract : Introduction: This study protocol outlines the evaluation of the pictorial support in person-centred care for children (PicPecc). PicPecc is a digital tool used by children aged 5–17 years to self-report symptoms of acute lymphoblastic leukaemia, who undergo high-dose methotrexate treatments. The design of the digital platform follows the principles of universal design using pictorial support to provide accessibility for all children regardless of communication or language challenges and thus facilitating international comparison. Methods and analysis: Both effect and process evaluations will be conducted. A crossover design will be used to measure the effect/outcome, and a mixed-methods design will be used to measure the process/implementation. The primary outcome in the effect evaluation will be self-reported distress. Secondary outcomes will be stress levels monitored via neuropeptides, neurosteroids and peripheral steroids indicated in plasma blood samples; frequency of in-app estimation of high levels of distress by the children; children's use of analgesic medicine and person centeredness evaluated via the questionnaire Visual CARE Measure. For the process evaluation, qualitative interviews will be carried out with children with cancer, their legal guardians and case-related healthcare professionals. These interviews will address experiences with PicPecc in terms of feasibility and frequency of use from the child's perspective and value to the caseworker. Interview transcripts will be analysed using an interpretive description methodology. Ethics and dissemination: Ethical approval was obtained from the Swedish Ethical Review Authority (reference 2019-02392; 2020-02601; 2020-06226). Children, legal guardians, healthcare professionals, policymaking and research stakeholders will be involved in all stages of the research process according to Medical Research Council's guidelines. Research findings will be presented at international cancer and paediatric conferences and published in scientific journals. Trial registration: ClinicalTrials.gov; NCT04433650 .